Resistance exercise with different workloads have distinct effects on cellular respiration of peripheral blood mononuclear cells - Emilia Ilona Lähteenmäki; Max Koski; Iida Koskela; Elias Lehtonen; Anna Kankaanpää; Heikki Kainulainen; Simon Walker; Maarit Lehti (Physiological Reports, 2022)
Abstract Little is known how acute exercise‐induced inflammation and metabolic stress affect immune cell bioenergetics and the portion of its components. Therefore, we investigated acute effects of eccentric‐only (E), concentric‐only (C) and combined eccentric‐concentric resistance exercise (E + C) bouts on cellular respiration of peripheral blood mononuclear cells (PBMCs). Twelve strength‐trained young men performed bench press resistance exercises in randomized order. Venous blood samples were drawn at pre‐, 5 min post‐ and 24 h post‐exercise. Several PBMC respiration states were measured using high‐resolution respirometry. Levels of leukocytes, interleukin 6 (IL‐6), C‐reactive protein (CRP), creatine kinase (CK), blood lactate and maximum voluntary isometric force were measured from the same time points. Effects of blood lactate and pH change on bioenergetics of PBMCs were investigated ex vivo. PBMC routine respiration (p = 0.017), free routine capacity (p = 0.025) and ET‐capacity (p = 0.038) decreased immediately after E + C. E responded in opposite manner 5 min post‐exercise compared to E + C (p = 0.013) and C (p = 0.032) in routine respiration, and to E + C in free routine activity (p = 0.013). E + C > C > E was observed for increased lactate levels and decreased isometric force that correlated with routine respiration (R = −0.369, p = 0.035; R = 0.352, p = 0.048). Lactate and pH change did not affect bioenergetics of PBMCs. Acute resistance exercise affected cellular respiration of PBMCs, with training volume and the amount of metabolic stress appear influential. Results suggest that acute inflammation response does not contribute to changes seen in cellular respiration, but the level of peripheral muscle fatigue and metabolic stress could be explaining factors.